Selenium donors inhibits osteoclastogenesis through inhibiting IL-6 and plays a pivotal role in bone metastasis from breast cancer. Issue 4 (13th August 2020) - Zhang, Luyan; Wu, Xifa; Feng, Yong; Zheng, Linlin; Jian, Jinbo
Abstract: Bone metastases are a frequent complication of breast cancer, and there has been little progress in the treatment of breast cancer patients with bone metastases. The cytotoxicity of selenium donors, including organic selenium and selenium nanoparticles (SeNPs), to cancer cells has been reported previously, but their relationship with bone metastases progression is not fully clear yet. In this study, multicenter clinical exploration was conducted to obtain dietary selenium intakes of breast cancer patients with or without bone metastasis, to study the relationship between selenium and breast cancer prognosis and bone metastasis. We found that dietary selenium intakes were significantly lower in breast cancer patients with bone metastasis, comparing with the non-bone metastasis cases. Selenium lower group of bone metastasis breast cancer patients had worse prognosis, whereas the daily selenium intakes could not predict the prognosis of breast cancer patients without bone metastasis. Subsequently, we study the regulatory role of selenium donors on bone metastasis at the cellular level, by challenging the cells with SeNPs. SeNPs showed potent cytotoxicity in breast cancer cells, no matter whether they were primary or bone-metastatic. SeNPs treated cancer cell inhibited the survival and differentiation of osteoclast progenitor cells. At the molecular level, we demonstrated that IL-6 partially mediated osteoclastogenesis suppression by SeNPs. These results provide a new way for biomarkers or drug development to treat and even prevent bone metastases of breast cancer by using selenium donors.